Performance of Delefilcon A Daily Disposable Contact Lenses in a Group of Digital Device Users - Wong S; Woods J; Schulze MM; Fadel D; Stahl U; Jones L (Clinical Ophthalmology)
Stephanie Wong, Jill Woods, Marc-Matthias Schulze, Daddi Fadel, Ulrike Stahl, Lyndon Jones Centre for Ocular Research & Education (CORE), School of Optometry & Vision Science, University of Waterloo, Waterloo, CanadaCorrespondence: Stephanie Wong, Centre for Ocular Research & Education (CORE), School of Optometry & Vision Science, University of Waterloo, Waterloo, Canada, Tel +1 519-888-4742, Fax +1-519-888-4303, Email s99wong@uwaterloo.caPurpose: To assess the performance of delefilcon A daily disposable contact lenses (CL) in lens wearers who reported heavy digital device use.Patients and Methods: This prospective study involved lens wearers who used digital devices ≥ 8 hours per day. Delefilcon A CL were dispensed for 2-weeks, to be worn ≥ 5 days/week, ≥ 13 hours/day, using digital devices as normal. At-home questionnaires rating comfort, dryness, and clarity of vision (0– 100 scale, 100=best) were completed on Days 1, 7, and 14± 1 upon insertion, after 8 hours of device use, and before removal. At the Day 14 visit, participants rated overall comfort, dryness, and vision (0– 100 scale) and completed a 5-point Likert-type scale questionnaire.Results: Thirty-five participants were eligible, 32 completed (27 females; age: 25.3± 6.3 years). Median at-home ratings for comfort, dryness, and vision were ≥ 85, with no difference between days (all p≥ 0.09). Ratings decreased throughout the day (p≤ 0.005), except comfort (Day 7) and vision (Days 1 and 7), where ratings before removal were similar to 8 hours of device use (p≥ 0.014). After 2-weeks, median (range) overall ratings for comfort, dryness, and vision were 96 (70– 100), 93 (50– 100), and 95 (75– 100), respectively. Most agreed the CL performed well, providing good comfort (91%) and vision all-day-long (94%), and did not have dryness with device use (69%). When devices were used ≥ 8 hours, most felt the CL performed well (84%), were satisfied with comfort (88%) and vision (88%), did not experience eye strain (81%), eye fatigue (66%), or episodes of blurred vision (75%).Conclusion: Delefilcon A lenses provided high satisfaction levels among lens wearers who spent a significant portion of their day using digital devices. Participants rated the CL highly for comfort and vision throughout the day, with most reporting no issues with dryness, eye strain, or blurred vision while wearing lenses and using digital devices.Keywords: comfort, vision, digital device, delefilcon A, daily disposable, contact lens